The Transcriptome of Utricle Hair Cell Regeneration in the Avian Inner Ear - Ku, Yuan-Chieh (Society for Neuroscience, 2014)
Sensory hair cell loss is the major cause of hearing and balance disorders. Mammals are incapable of sustained hair cell regeneration, but lower vertebrates can regenerate these mechano-electrical transducers. We present the first comprehensive transcriptome (by mRNA-Seq) of hair cell regeneration in the chick utricle. We provide pathway and pattern annotations and correlate these with the phenotypic events that occur during regeneration. These patterns are surprisingly synchronous and highly punctuated. We show how these patterns are a new resource for identifying components of the hair cell transcriptome and identify 494 new putative hair-cell-specific genes and validate three of these (of three tested) by immunohistochemical staining. We describe many surprising new components and dynamic expression patterns, particularly within NOTCH signaling. For example, we show that HES7 is specifically expressed during utricle hair cell regeneration and closely parallels the expression of HES5. Likewise, the expression of ATOH1 is closely correlated with HEYL and the HLH inhibitory transcription factors ID1, ID2, and ID4. We investigate the correlation between fibroblast growth factor signaling and supporting cell proliferation and show that FGF20 inhibits supporting cell proliferation. We also present an analysis of 212 differentially expressed transcription factor genes in the regenerative time course that fall into nine distinct gene expression patterns, many of which correlate with phenotypic events during regeneration and represent attractive candidates for future analysis and manipulation of the regenerative program in sensory epithelia and other vertebrate neuroepithelia.